2017
DOI: 10.1080/13603124.2017.1394496
|View full text |Cite
|
Sign up to set email alerts
|

School district support to schools: voices and perspectives of school principals in a province in South Africa *

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
2
18
0
4
Order By: Relevance
“…Desde este enfoque, la base del trabajo conjunto entre profesionales de escuelas y profesionales de agencia de nivel intermedio es el aprendizaje profesional. Además, el concepto de liderazgo pedagógico de todo el sistema (Bantwini & Moorosi, 2017) resuena con este enfoque, entendiendo que el foco de este liderazgo es mantener la enseñanza y aprendizaje como criterio principal de la toma de decisiones. En particular, estudios indican como prácticas el modelamiento situado y en la acción, la elaboración y uso de herramientas locales, la amortiguación de diferentes solicitudes, la intermediación con otros actores y agencias locales, y la mantención en el tiempo de la comunicación y atención para un trabajo conjunto.…”
Section: ¿Qué Son Las Agencias De Educación Públicas De Nivel Interme...unclassified
See 1 more Smart Citation
“…Desde este enfoque, la base del trabajo conjunto entre profesionales de escuelas y profesionales de agencia de nivel intermedio es el aprendizaje profesional. Además, el concepto de liderazgo pedagógico de todo el sistema (Bantwini & Moorosi, 2017) resuena con este enfoque, entendiendo que el foco de este liderazgo es mantener la enseñanza y aprendizaje como criterio principal de la toma de decisiones. En particular, estudios indican como prácticas el modelamiento situado y en la acción, la elaboración y uso de herramientas locales, la amortiguación de diferentes solicitudes, la intermediación con otros actores y agencias locales, y la mantención en el tiempo de la comunicación y atención para un trabajo conjunto.…”
Section: ¿Qué Son Las Agencias De Educación Públicas De Nivel Interme...unclassified
“…En efecto, los casos que han estudiado este tema identifican a lo menos los siguientes movimientos: se ubican a profesionales a cargo del apoyo en un nivel de alta responsabilidad dentro de la agencia local, la asignación de recursos se encuentra alineada con las prioridades y enfoque de mejora de esta agencia, se definen tiempos protegidos para el apoyo técnico con escuelas, y se definen y revisan criterios para la distribución del número de establecimientos que apoya cada líder intermedio. Por el contrario, se presentan estudios que dan cuenta que la mayor insatisfacción respecto del apoyo del distrito reportado por directores escolares se explica por las dificultades en la provisión de recursos y de oportunidades de desarrollo profesional, la falta de visibilidad del distrito y la capacidad de respuesta al cambio, lo que en conjunto genera pérdida de confianza en el trabajo distrital (Bantwini & Moorosi, 2017). Igualmente, estudio de casos dan cuenta que diseños organizacionales tradicionales o con menos sustento en nuevos conocimientos sobre el apoyo pueden influir en un desarrollo estratégico y operativo débil de la asistencia técnica pedagógica en el territorio (Anderson et.…”
Section: ¿Qué Son Las Agencias De Educación Públicas De Nivel Interme...unclassified
“…Furthermore, the Physical Sciences teacher for School D indicated that the district officials in some instances come to the school to assess their material needs, promising to assist, but do not always come back to deliver on their promises (see Nkambule, & Amsterdam, 2018). Bantwini and Moorosi (2018a) corroborated this assertion by highlighting the lack of visibility, whereby district officials fail to respond or follow up to provide the services that schools expect of them. School A's Mathematics teacher tapped into the conversation of poor visibility of district officials by saying that "the subject advisor said that if you [we] have a problem in this topic, [we should] email them so that they can see their programmes … [to] come and teach that topic … but it's rare".…”
Section: The Role Of the District Education Officementioning
confidence: 99%
“…Although district officials play phenomenal roles in enhancing curriculum implementation (Bantwini, & Diko, 2011), their visibility (Bantwini, & Moorosi, 2018a) and lack of follow-ups are under criticism (Taole, 2013). They are criticised for poor responses to challenges identified or raised by schools.…”
Section: Introductionmentioning
confidence: 99%
“…The prominence of district-level leadership for student's achievement (Leithwood et al, 2019) and school improvement (George and Kincaid, 2008;Wilkinson et al, 2019) has been accounted for as well as for various professional support services to school leaders and teachers (Bantwini and Moorosi, 2018;Ikemoto et al, 2014;Louis et al, 2010). Furthermore, the importance that this leadership be proactive rather than reactive in nature is well established by Hargreaves and Shirley (2020).…”
Section: Introductionmentioning
confidence: 99%